Implementation of Primary Nursing Care Method and Nurses’ Work Satisfaction - Hesti Rahayu; Tri Kurniati; Giri Widakdo (NERS Jurnal Keperawatan, 2025)
The primary nursing care method enhances job satisfaction by giving nurses greater autonomy in patient management. This study aims to analyze the relationship between primary nursing care implementation and nurse job satisfaction in a general hospital inpatient ward. This cross-sectional quantitative study included all 58 inpatient nurses at a general hospital using total sampling. Conducted in November 2024, it targeted nurses working in inpatient units implementing the Primary Nursing Care Method who agreed to participate. The study involved 58 nurses, mostly aged 25-34 years (79.3%), female (96.6%), with a Nurse degree (77.6%), and 1-4 years of experience (46.6%). Recognition was received by 51.7% of nurses. A significant relationship was found between primary nursing care implementation and job satisfaction (p = 0.011, OR = 1.115). Implementing primary nursing care is associated with higher job satisfaction, increasing the likelihood by 1.115 times compared to non-implementation. The general hospital should implement training, supervision, and evaluations for primary nursing care while strengthening nurse appreciation through managerial support and periodic awards.